Synthesis and Application of NaNi0.5Ti0.5O2 as Electrode Material for Sodium Ion Batteries - Nghia, Nguyen Van; Thao, Pham Manh; Ky, Nguyen Van; Quyen, Ngo Quy; Long, Pham Duy; Chien, Dang Tran; Hieu, Nguyen Si (VNU Journal of Science: Natural Sciences and Technology; Vol 38 No 3DO - 10.25073/2588-1140/vnunst.5186, 2022)
In this work, NaNi 0.5 Ti 0.5 O 2 cathode materials of sodium ion batteries were synthesized by a pre-milling combined with solid-state reaction method using sodium hydroxide (NaOH), nickel (II) acetate (2(CH 3 COO)Ni.4H 2 O), and titanium dioxide (TiO 2 ) as the precursors. Results of X-ray diffraction analysis of the materials obtained after the milling and calcination processes revealed that the increment of the pre-milling time improved the reactivity of NaOH and TiO 2 , thereby significantly reduced the content of NiO impurity in the NaNi 0.5 Ti 0.5 O 2 product. The as-synthesized cathode material possessed an excellent electrochemical performance with 77% capacity (compared to the second cycle) retained after 50 cycles of charge/discharge, and 60% capacity retention when the rate of charge/discharge increased from 0.5 to 8 C.